Esterification of Free Fatty Acids in Waste Cooking Oil by Heterogeneous Catalysts - 刘丽艳 刘志敏 唐国武 谭蔚 (Transactions of Tianjin University, 2014)
Waste cooking oil （WCO） is becoming the most promising alternative feedstock to produce biodiesel due to its low cost in China. In this study, NKC-9 ion-exchange resin and H-beta zeolite were selected as heterogeneous catalysts in the WCO esterification process and their esterification characteristics were compared by orthogonal ex- periments. NKC-9 resin showed higher activity and achieved a higher final conversion compared with H-beta zeolite under the same reaction conditions. Reusability experiments showed that NKC-9 resin still exhibited high activity after 5 runs. The effects of the mole ratio of alcohol to oil, reaction time, reaction temperature and the catalyst dose were investigated by multifactor orthogonal analysis. The influence of the free fatty acid （FFA） content was also investi- gated, and the result showed that the esterification rate could be as high as 98.4% when the FFA content was 6.3wt%.